Seasonal variation of anti-Leishmania infantum antibodies and laboratory abnormalities in dogs with leishmaniosis - Maria Alfonsa Cavalera; Annamaria Uva; Mariaelisa Carbonara; Jairo Alfonso Mendoza-Roldan; Xavier Roura; José Joaquín Cerón; Domenico Otranto; Andrea Zatelli (Parasites & Vectors)
Abstract Background In dogs affected by leishmaniosis, laboratory abnormalities and anti-Leishmania antibody titers are crucial for initial and relapse diagnosis, as well as for informing therapeutic decisions. This study aimed to evaluate laboratory findings in L. infantum seropositive dogs during and after the transmission season on the basis of the evidence that anti-L. infantum antibody titers vary between sand fly and nonsand fly transmission periods in dogs from areas where leishmaniosis is endemic. Methods In September 2021 (transmission season; T1) and January 2022 (nontransmission season; T2), L. infantum seropositive dogs were physically examined, and blood sampling was performed for laboratory tests. At both time points, dogs underwent routine hematology, a complete biochemical panel including acute phase proteins (i.e., C-reactive protein [CRP] and ferritin), erythrocyte sedimentation rate [ESR] measurement, serum capillary electrophoresis, and serology for L. infantum. Potential coinfections with other arthropod-borne (Anaplasma phagocythophilum, Ehrlichia canis, Dirofilaria spp.) and snail-borne (Angiostrongylus vasorum) pathogens were also excluded. Results Total protein and CRP levels were slightly reduced in T2 compared with T1, although the difference was not statistically significant. Antibody titers also decreased in 10 out of 18 dogs (55.5%), with two (20%) becoming seronegative, while they remained constant in eight out of 18 dogs (44.4%). Furthermore, a statistically significant reduction was observed in globulin percentage, ferritin, and ESR, whereas albumin percentage and total iron levels significantly increased. Conclusions Anti-L. infantum antibody titers and laboratory abnormalities in seropositive dogs living in endemic areas for leishmaniosis may vary. This variation may be related to vector seasonality and, consequently, dogs’ exposure to sand fly saliva and potential reinfections. These results reinforce the importance of considering the sampling season in the clinical evaluation and management of dogs affected by leishmaniosis to avoid misdiagnosis and unnecessary antileishmanial treatments. Graphical Abstract